Penerapan Psikologi Positif pada Dunia Kerja dalam Meningkatkan Kecerdasan Emosional Karyawan - Farida Ulyani; AM. Diponegoro; Nina Zulida Situmorang (Journal of Economics and Management Scienties, 2023)
The era of the Industrial Revolution 4.0 hit most of the companies that transformed from conventional concepts to virtual based (digitalization). To achieve the goals of the organization or company still need humans as one of the resources. Organizational achievements can be achieved with human expertise, experience and knowledge. The ability to achieve goals within the company properly in maintaining the stability of the company for the short and long term as well as in its growth is part of the benchmark for the success of a company. This article aims to analyze the application of positive psychology in the world of work in increasing employee emotional intelligence. This research uses library research, this article uses books and scientific journals as well as secondary data as data. In this article, detailed data sources include information that is appropriate to the focus on the study and the chosen theme.